Praktikalitas Penggunaan Media Sosial Pembelajaran Edmodo untuk Program Remedial dan Forum Diskusi Guru - Zonalia Fitriza; Iswendi Iswendi; Iryani Iryani; Faizah Qurratul ‘Aini (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Remedial program is given to the students who do not pass the minimum criteria of learning result. Based on the “KTSP” Technical guidance evaluation in 2008 and 2009, generally teacher only gave retest to the student who didn’t pass the examination, without giving any treatment to pass the learning outcome which was not pass before. It happened because there wasn’t enough time to do this program. The solution was by using learning social media Edmodo which can be accessed online, so the students can do remedial program whenever and wherever they want without preparing remedial time at school. So, the Chemistry teachers in Kabupaten Solok was trained to use edmodo for remedial program. Besides, this media was also used for online teacher forum. This training was evaluated through questioner about practicality of social media edmodo for remedial program and online teacher forum. The result was analyzed by Kappa Cohen Formula with the value of k is 0,7, it means has high practice value.